A RETROSPECTIVE STUDY ON PATIENTS UNDERGOING PARATHYROIDECTOMY FOR PRIMARY HYPERPARATHYROIDISM - Wong, Liang Wei; Sambamoorthy, Vijayrama Rao; Rahim, Anilah Abdul; Rahmatullah, Ijaz Hallaj (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Primary hyperparathyroidism (PHPT), characterized by hypercalcemia with elevated or inappropriately normal parathyroid hormone (PTH) level, has an estimated incidence of one to seven per 1000 adults. Parathyroidectomy remains the only definitive treatment and offers cure for this condition. METHODOLOGY A retrospective study was done to determine the demographic and clinical severity of patients undergoing parathyroidectomy in Hospital Raja Permaisuri Bainun (HRPB), and its surgical outcomes. A retrospective study was done for all patients with PHPT who underwent parathyroidectomy in HRPB, from the year 2018-2023. Demographics, laboratory and radiologic investigations including levels of serum PTH, serum adjusted calcium, serum alkaline phosphatase, and postoperative complications were recorded from patients’ admission notes and electronic medical records and were analysed using SPSS. RESULTS Twenty-five patients with a mean age of 58.8 ± 9.4 years were included in the study, of which, 72% were female. Of the total, 76% had a single parathyroid adenoma, 12% had parathyroid hyperplasia and 12% had parathyroid carcinoma. Pre-operative mean serum calcium was 2.86 ± 0.26 mmol/L, mean serum alkaline phosphatase was 104 ± 87 IU/L, while pre-operative median PTH level was 38.38 pmol/L (interquartile range = 68.63). Parathyroid lesions were localized by ultrasound of the neck (87.5%) and by parathyroid scintigraphy (88.9%). Complications included osteoporosis (57.1%) and nephrolithiasis (52.6%). Sixty percent received calcium supplementation during the immediate postoperative period. Two patients developed post-operative hypocalcaemia, two had neck hematoma and one was complicated with recurrent laryngeal nerve palsy. CONCLUSION Half of our patients were diagnosed with PHPT-related complications prior to surgery, suggesting a need for better screening strategies. Parathyroidectomy offers high cure rates for primary hyperparathyroidism in the hands of experienced surgeons and should be recommended to patients meeting the criteria for surgery.